AsES elicitor induces ethylene production, accelerates ripening, and prevents Botrytis cinerea rot in strawberry fruit - Perato, Silvia Marisa; Furio, Ramiro Nicolas; Tomas-Grau, Rodrigo H.; Salazar, Sergio Miguel; Díaz Ricci, Juan Carlos; Martinez Zamora, Martin Gustavo (Springer, 2022)
AsES (Acremonium strictum Elicitor Subtilisin) is a fungal subtilase that induces a defense response in Arabidopsis thaliana and in many commercial crops. Recently, we demonstrated that AsES is also able to accelerate ripening in a climacteric fruit like avocado by regulating the ethylene signaling pathway. The aim of the present work was to investigate AsES effect on the maturation and postharvest quality of a non-climacteric fruit like strawberry. The involvement of ethylene was evaluated using the ethylene perception inhibitor 1-methylcyclopropene (1-MCP). Results obtained showed that fruit treated with AsES induced ethylene synthesis, weight loss, color change, soluble solids content and titratable acidity, but did not affect the respiration rate. Experiments were carried out using fruit at different ripening stages e.g. white, pink and red fruit. However, when using 1-MCP, the endogenous production of ethylene and the respiration rate increased strongly in white fruit, without changing the other ripening parameters. Also, treatment of red fruit with AsES alone prevents the development of gray mold disease caused by B. cinerea, improving postharvest quality. However, the fruit protection achieved by AsES is prevented when ethylene perception is inhibited with 1-MCP. The AsES elicitor induces ethylene biosynthesis and regulates physiological ripening parameters in strawberry fruit; however it does not affect the respiration rate. Results obtained indicate that active ethylene receptors are necessary to activate an AsES-induced defense response against gray mold disease, and to control its biosynthesis.